The Public-Private Partnerships (PPP): The Case Of The Brics Countries - Djakhongir Makhmudjon ogly, Takhirov (Research Parks Publishers, 2023)
This research study provides a comparative examination of several partnership types and looks at how well public-private partnerships (PPPs) benefit small and medium-sized enterprises (SMEs). Finding the best strategies for fostering SME expansion is the goal. The paper examines how PPPs might support the development of SMEs, acknowledging their critical role in generating employment and economic progress. The research looks at governance structures, finance mechanisms, resource allocation, knowledge sharing, and capacity building as important elements influencing partnership success by analyzing several PPP models across different countries and industries. The report presents recommendations for decision-makers in government, business, and agency that support small and medium-sized enterprise development. It also sheds light on the advantages, disadvantages, and best practices of various partnership arrangements. The study adds to our understanding of PPPs and SME assistance while offering useful suggestions for improving public-private sector cooperation. The results have important ramifications for shaping public policy and directing the creation and execution of successful PPPs that assist SMEs and promote long-term economic growth and prosperity.